D,L‐3‐hydroxybutyrate in the treatment of glucose transporter 1 deficiency syndrome (Glut1DS) - Aya Amer; Kathryn Murrell; Liza Edmonds; Isaac Bernhardt; Rhonda Akroyd; Bryony Ryder; Callum Wilson; Emma Glamuzina (JIMD Reports)
Abstract Background Deficiency of the Glut1 transporter due to mono‐allelic variants in SLC2A1 causes hypoglycorrhachia, resulting in a neurological spectrum from neonatal epilepsy to adult‐onset paroxysmal movement disorders (PMD). The brain utilises ketone bodies as an alternative energy source to glucose. Thus, early initiation of the ketogenic diet (KD) is standard care for Glut1 deficiency syndrome (Glut1DS). Commencement and adherence in older Glut1DS patients is difficult to achieve, leaving few treatment options. Oral D,L‐3‐hydroxybutyrate (D,L‐3‐HB) crosses the blood–brain barrier, making it a potential treatment for Glut1DS. Methods A retrospective case review of patients with Glut1DS under the Adult and Paediatric National Metabolic Service (APNMS) of New Zealand, treated with D,L‐3‐HB between 2012 and 2023 was performed. Clinical notes, standardised, neuropsychological assessments and subjective data on and off D,L‐3‐HB were obtained. The best on and off D,L‐3‐HB measures of working memory (WMI) and processing speed (PSI) were compared to assess the efficacy. Results D,L‐3‐HB was offered to 12 patients with Glut1DS (age 10–52 years). Compliance‐dependent improvements in subjective, cognitive and adaptive function were reported by those who were reassessed on‐treatment (9/12). Four reported improved PMD. Objective improvements were found in WM (9/9) and PS (6/9). Subjective improvements were reported in patients' health, wellbeing and independence. Conclusions KD remains standard of care for Glut1DS, but effective alternatives are lacking for those who do not tolerate this. D,L‐3‐HB was associated with improved WM, PS and perceived life quality in this small group of patients with Glut1DS, thus providing a potential treatment for this distinct group.